Effects of Curcumin Against Matrix Metalloproteinase-2 (MMP-2) and Tissue Inhibitor Metalloproteinase-2 (TIMP-2) Serum Level on Rat Model of Liver Fibrosis Resolution Process - Supriono Supriono; Bogi Pratomo; Muhammad Kriestian (The Indonesian Society for Digestive Endoscopy, 2018)
Background: Liver fibrosis is an effect from continuous fibrogenesis and fibrolysis process. During fibrogenesis, MMP-2 and TIMP-2 that produced by hepatic stellate cell (HSC) have a role to regulate extracellular matrix (ECM) homeostastic. Otherwise, curcumin inhibits both MMP-2 and TIMP-2 expression and enhances HSC apoptosis, thus inhibit fibrogenesis. Role of curcumin, MMP-2, and TIMP-2 in a fibrolysis process has not been widely studied. This study aimed to determine the correlation between curcumin administration and the decline of MMP-2 and TIMP-2 on rat model of liver fibrosis.Method: This is an experimental study done in male Wistar rats. There are 8 groups consist of 4 rats each. Both control and intervention group were exposed to CCl4 1 cc/kgBW intraperitoneally 2 times per week for 9 consecutive weeks to form F3 fibrosis. Negative control group was injected with normal saline. After CCl4 injection, control group was given curcumin solvent as placebo while intervention groups were given curcumin 200 mg/kgBW for 2, 5, and 9 weeks. Statistical analysis then conducted in the end of study. Results: MMP-2 and TIMP-2 were remarkably increased in positive control group, but found decreased in control group 5 and 9. There are remarkable decrease of MMP-2 and TIMP-2 serum level in intervention group 2, 5, and 9, but MMP-2 and TIMP-2 level was significantly lower in intervention group 2 compared to the control group.Conclusion: MMP-2 and TIMP-2 serum level were decreased after giving of curcumin for 2 weeks. The duration of curcumin administration correlated with decrease of TIMP-2 serum level but not correlated with MMP-2 serum level in rat model of liver fibrosis.